PERSPEKTIF FILOSOFIS DALAM PENDIDIKAN: - ARI SANDI; ENI ELYATI; KASINYO HARTO; MARDIAH ASTUTI (Raudhah - Proud To Be Professional, 2022)
This article tries to examine the philosophy of education whose scope includes ontology, epistemology and educational axiology. Educational ontology examines the nature of education. Educational epistemology discusses the origins or sources of education, methods of building education, elements of educational goals, and so on. Meanwhile, educational axiology examines the use-value of education. The essence of education is a conscious effort to guide and develop the potential and personality and basic abilities of students towards a noble personality and noble character. The truth of education is shown in the output or results of the whole series of education according to formal objects, methods and systems, namely in the form of intellectual intelligence, emotional intelligence and spiritual intelligence possessed by students.